Impact of Falls and Fear of Falling on Participation, Autonomy and Life Satisfaction in the First Year After Spinal Cord Injury - Chan, Katherine; Habib Perez, Olinda; Singh, Hardeep; Marinho-Buzelli, Andresa R.; Hitzig, Sander L.; Musselman, Kristin E. (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Individuals with spinal cord injury (SCI) experience reduced participation in meaningful activities, leading to reduced social engagement and negative psychological impact. Two factors that may affect participation post-SCI are fall status (e.g., having experienced a fall) and having a fear of falling. Our objective was to examine if and how fall status and fear of falling impact participation, autonomy and life satisfaction in the first year post-injury. Methods: Adult inpatients of a SCI rehabilitation hospital were recruited. Following discharge, falls were tracked for six months and participants who fell at least once were categorized as ‘fallers’. At the end of the six-month period, the Impact on Participation and Autonomy Questionnaire and Life Satisfaction Questionnaire 9 were administered, and participants were asked if they had a fear of falling (i.e., an ongoing concern about falling leading to the avoidance of activities they are capable of doing). Falls were reported using descriptive statistics. Ordinary least squares regression was used to evaluate the relationships between the independent variables (i.e., fall status and fear of falling) and each dependent variable (i.e., questionnaire scores). Results: Seventy-one individuals were enrolled in the study; however, 11 participants were lost to follow-up. The included participants (n=60) were 58.4 ± 14.6 years old and 99 ± 60.3 days post-injury. Over one third (38.3%) of participants fell over the six-month tracking period. Twenty-seven participants (45%) reported a fear of falling and 14 (51.9%) of these participants were fallers. Fear of falling significantly predicted scores of autonomy indoors (β=3.38, p=0.04), autonomy outdoors (β=2.62, p=0.04) and family role (β=3.52, p=0.05). Conclusion: Individuals with subacute SCI and a fear of falling experienced reduced participation and autonomy, but with no differences in life satisfaction compared to those without a fear of falling. In contrast, having experienced a fall did not impact participation, autonomy or life satisfaction. In the first year after SCI, rehabilitation programs should place specific attention on the presence of fear of falling to help individuals with SCI prepare for everyday mobility challenges.